Can ESR be a diagnostic marker for assessing the severityof malarial infection? A retrospective study - Patil, Asha; Muduthan, Vivek Raghavan; Kunder, Gunavathi (Bangladesh Journal of Medical Science, 2019)
Objective: This study aimed to investigate the variation of ESR in malarial infection and find out the variation of ESR in related to the degree of parasitemia. Material and Methods: A retrospective study with a duration of 6 months, on 385 randomly selected positive malaria cases. Their clinical record and lab records were analyzed for ESR level. Result: The sample of 385 positive malaria cases has included both males and females, ages ranged from 15-60 years old. A total number of Plasmodium.falciparumwas 60 (uncomplicated & severe cases) and for Plasmodiumvivax was 325. In P.vivax infection the raised values were seen in 174 cases (53.5%) and in P. falciparum infection it was seen in 36 cases (60%). The degree of parasitemia did not show any significant rise in ESR in case of malarial infection. Conclusion: In our investigation, the degree of parasitemia did not show a significant rise in ESR except in the case of occasional parasitemia. We assume that the rise in ESR may be due to inflammatory process during infection or due to the presence of inclusion bodies Bangladesh Journal of Medical Science Vol.18(4) 2019 p.756-759